Efficacy of a Novel Method for Inspiratory Muscle Training in People With Chronic Obstructive Pulmonary Disease. Issue 9 (1st September 2015) - Langer, Daniel; Charususin, Noppawan; Jácome, Cristina; Hoffman, Mariana; McConnell, Alison; Decramer, Marc; Gosselink, Rik
Abstract : Background: Most inspiratory muscle training (IMT) interventions in patients with chronic obstructive pulmonary disease (COPD) have been implemented as fully supervised daily training for 30 minutes with controlled training loads using mechanical threshold loading (MTL) devices. Recently, an electronic tapered flow resistive loading (TFRL) device was introduced that has a different loading profile and stores training data during IMT sessions. Objective: The aim of this study was to compare the efficacy of a brief, largely unsupervised IMT protocol conducted using either traditional MTL or TFRL on inspiratory muscle function in patients with COPD. Design: Twenty patients with inspiratory muscle weakness who were clinically stable and participating in a pulmonary rehabilitation program were randomly allocated to perform 8 weeks of either MTL IMT or TFRL IMT. Methods: Participants performed 2 daily home-based IMT sessions of 30 breaths (3–5 minutes per session) at the highest tolerable intensity, supported by twice-weekly supervised sessions. Adherence, progression of training intensity, increases in maximal inspiratory mouth pressure (Pi max), and endurance capacity of inspiratory muscles (Tlim) were evaluated. Results: More than 90% of IMT sessions were completed in both groups. The TFRL group tolerated higher loads during the final 3 weeks of the IMT program, with similar effort scores on the 10-Item Borg Category Ratio (CR-10) Scale, and achieved larger improvements in Pi max and Tlim than the MTL group. Limitations: A limitation of the study was the absence of a study arm involving a sham IMT intervention. Conclusions: The short and largely home-based IMT protocol significantly improved inspiratory muscle function in both groups and is an alternative to traditional IMT protocols in this population. Participants in the TFRL group tolerated higher training loads and achieved larger improvements in inspiratory muscle function than those in the MTL group.